MEKANISME PEMOTONGAN, PENYETORAN, DAN PELAPORAN PPh PASAL 23 ATAS JASA PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (DPUPR) BANJARMASIN - Septina Putri Parsiah; Siti Mutmainah Zulfaridatulyaq (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
This study aims to determine the mechanism of withholding, filing and reporting PPh 23 DPUPR Banjarmasin. In recent years, the growth of regional original income (PAD) has increased very well. Income Tax Certificate (PPh 23), as described in the law, so that the Banjarmasin DPUPR can fulfill its income tax obligations, such as withholding Article 23 of Income Tax on payments determined by law and tariff procedures, which must be complied with by interested parties. This research was conducted with the aim of knowing the mechanism for withholding, depositing, and reporting income tax article 23.